(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article shows the selection and orientation of the student youth in the sport of badminton in the training group, the minimum and maximum number of students in the group, the maximum age of admission to the training. In addition, systematic coverage of the annual periods of the training group, the estimated hours of loads passed throughout the year, the expenditure on the preparatory types of loadings